Spatial modeling of greenhouse gas emissions from burning biomass in the residential sector in Volyn region - Danylo, Olha; Lyubinsky, Bogdan (Видавництво Львівської політехніки, 2013)
Spatial model of greenhouse gas emissions from burning biomass in the residential sector in Volyn region is developed. The results of modeling are analysed. The major emission sources are located. Based on performed numerical experiments the digital map and georeferenced databases, containing information about the sources and evaluation of the greenhouse gas emissions, are obtained.
Keywords: spatial modeling; residential sector; greenhouse gas emissions; biomass; Volyn region; global warming